Nilai-Nilai Pembelajaran Sejarah Masyarakat Adat Kajang: Studi Etnografi Nilai Falsafah Pasang Ri Kajang - Amirullah, Amirullah; Ridha, Muh. Rasyid; Wati, Fitra Widya; Kabubu, Rusmala Dewi; Sumardin, Oschar (Jambura History and Culture Journal, 2025)
Pasang ri Kajang is a philosophy of life embraced by the Ammatoa Kajang indigenous community in Bulukumba, South Sulawesi. This concept not only governs social and cultural aspects but also serves as a guideline for maintaining balance between humans and nature. This study employs a qualitative research method with an ethnographic approach to explore the meaning and practice of Pasang ri Kajang in the daily lives of the Kajang people. Data were collected through direct observation, in-depth interviews with traditional leaders, and analysis of relevant documents and literature. The findings reveal that Pasang ri Kajang plays a crucial role in shaping collective identity, customary legal systems, and environmental sustainability. Values such as simplicity, honesty, and harmony with nature form the core of this philosophy. This study provides insight into how traditional value systems persist amid modernization and their relevance in development planning based on local wisdom.